Conceptualising entrepreneurship, innovation and late industrialisation: the state creation of entrepreneurs in Malaysia. (26th July 2011) - Tan, Jeff
Entrepreneurship is central to innovation and hence industrialisation. However, the innovation process is cumulative, increasingly undertaken within formal organisations, and characterised by uncertainty. The technological challenge facing developing country entrepreneurs attempting to 'catch up' is considerable in this context and can be supported by the appropriate institutions and policies. The efficacy of these will depend on the nature of the government – business relationship and whether the state can ensure such support is contingent upon learning taking place. Malaysia's attempts to create domestic entrepreneurs demonstrate the difficulties involved, and the importance of accounting for political factors.